PP.05.03: THE EFFECTS OF INITIAL AND SUBSEQUENT OVERWEIGHT OR OBESE ON HYPERTENSION. (June 2015) - Pan, P.; He, S.; Chen, X.
Abstract : Objective: The aims of our study were to examine whether becoming nonobese could reverse the adverse effects of initial overweight or obesity on hypertension in adulthood. Design and method: We collected the data in1992 and again in 2007 from the same group of 577 individuals. The subjects were classified into four groups: individuals with a normal BMI (body mass index) in 1992 and 2007 were in group I; those with a normal BMI in 1992 but overweight or obese in 2007 were in group II; those who were overweight or obese in 1992 but normal BMI in 2007 were in group III; and those who were kept overweight or obese in 1992 and 2007 were in group IV. Results: The cumulative incidence of hypertension was 36.2%, 62.2%, 38.7% and 62.0% for group I to IV, respectively. Compared with group I, the HR is 1.817 for group II (p < 0.001), 1.065 for group III (p = 0.746) and 2.254 for group IV (p < 0.001). There was not significantly different between groups I and III, and the same as between groups II and IV. Conclusions: Compared with the individual who persist being overweight or obesity, becoming nonobese could reverse the adverse effects of overweight or obesity on hypertension; compared with who were persisted in normal BMI, being overweight or obese will increase the morbidity of hypertension. In short, overweight or obese would increase the risk for hypertension, and loss weight might reverse the adverse effect.